Spatial variation of large industries in Iraq (Journal of the College of Basic Education, 2023)
Large industries have great importance because of their impact on the economic sector, so it is necessary to study their structure and geographical distribution, as this research came to identify their position and structure in Iraq, as well as their geographical distribution. (719) establishments for the year 2020, in addition to the increase in the number of workers in them, which reached (126,790) workers. New industries, while the rate of change in the number of workers decreased as a result of the referral of a large number of workers to retirement, and the research also touched on the structure of large industries in Iraq. Food ranked second, while other industrial branches decreased, such as the mining and quarrying industry, basic mineral industries, and wood industries. As for other indicators, the chemical industries came in first place. The spatial distribution of the total large industries in Iraq was studied, and with the help of several indicators, and it became clear that there is a discrepancy in This distribution is between the governorates of Iraq, and also a study of the spatial distribution of the branches of large industries in Iraq using the number of establishments index, as this distribution varied, as the number of establishments of certain industrial branches increased in certain governorates and the decrease of other branches, as a result of various factors and reasons, such as the increase in the number of industrial establishments food in Baghdad governorate due to the high number of the population and the availability of raw materials.